Amount of Zinc Transferred in Breast Milk to Breastfed Moroccan Babies with Normal or Low Birth Weight at 1, 3 and 6 Months After Birth - choua, Ghizlane; HALOUI, Nourddine EL; KARI, Khalid EL; AGUENAOU, Hassan; MOKHTAR, Najat (International Journal of Child Health and Nutrition, 2014)
The amount of zinc in breast milk is generally regarded as sufficient to cover the increasing zinc demands of most infants. However, this is not well investigated where stores zinc may be compromised in babies with low birth weight (LBW) who are born with low stores of zinc. In Morocco, this is the first time that the amount of zinc transferred in breast milk has been estimated. This study included 32 mother-baby pairs. In our case study, we aimed to measure The quantity of zinc in mothers’ breast milk with normal birth weight (NBW) and LBW babies who were exclusively or not exclusively breast fed at 1,3 and 6 month after birth. The results showed that the majority of mothers have a BMI ≥25 kg/m2 this means that all mothers are overweight during 6 months after birth. Zinc concentration (mg/l) in mothers’ breast milk decreased from first month to six month. p- value showed that for mothers with NBW babies, there is a significant difference between the 1 and 6 month (p=0.0003) and between 3 and 6 month after birth (p=0.0007). For mothers with LBW babies, p-value showed a significant difference between the zinc concentration in breast milk in the 1st and 3rd month (p=0.0007), 1 and 6 month (p< 0.0001) and between 3rd and 6th month after birth (p=0.0056). The rate of NBW babies who were exclusively breastfed was 36.67%, 30.25% and 10% successively in 1st, 3rd and 6th month after birth. For LBW babies, the rate of exclusively breastfed was 15.38%, 7.69% and 2.69% successively in 1st, 3rd and 6th month after birth. Based on the K. Brown study in 2009, we can develop a mathematical equation to our own population using our data: Ln [Zinc] = 0.960 – 0.161*Ln(âge) – 0.187*Ln(âge)2. In conclusion the zinc concentration in milk is within normal range and decreases with the age of the babies. The predicted model of zinc concentration in breast milk was developed and tested.